Possible role of calcitonin gene‐related peptide in trigeminal modulation of glomerular microcircuits of the rodent olfactory bulb - Genovese, Federica; Bauersachs, Hanke; Gräßer, Ines; Kupke, Janina; Magin, Laila; Daiber, Philipp; Möhrlen, Frank; Frings, Stephan (European journal of neuroscience, 2016)
Abstract Chemosensation in the mammalian nose comprises detection of odorants, irritants and pheromones. While the traditional view assigned one distinct sub?system to each stimulus type, recent research has produced a more complex picture. Odorants are not only detected by olfactory sensory neurons but also by the trigeminal system. Irritants, in turn, may have a distinct odor, and some pheromones are detected by the olfactory epithelium. Moreover, it is well?established that irritants change odor perception and vice versa. A wealth of psychophysical evidence on olfactory?trigeminal interactions in humans contrasts with a paucity of structural insight. In particular, it is unclear whether the two systems communicate just by sharing stimuli, or whether neuronal connections mediate cross?modal signaling. One connection could exist in the olfactory bulb which performs the primary processing of olfactory signals and receives trigeminal innervation. In the present study, neuroanatomical tracing of the mouse ethmoid nerve illustrates how peptidergic fibers enter the glomerular layer of the olfactory bulb, where local microcircuits process and filter the afferent signal. Biochemical assays reveal release of calcitonin gene?related peptide from olfactory bulb slices and attenuation of cAMP signaling by the neuropeptide. In the non?stimulated tissue, the neuropeptide specifically inhibited the basal activity of calbindin?expressing periglomerular interneurons, but did not affect the basal activity of neurons expressing calretinin, parvalbumin, or tyrosine hydroxylase, nor the activity of astrocytes. This study represents a first step toward understanding trigeminal neuromodulation of olfactory?bulb microcircuits and provides a working hypothesis for trigeminal inhibition of olfactory signal processing.
Gesehen am 03.05.2018